Correlation of Antagonistic Regulation of leuO Transcription with the Cellular Levels of BglJ-RcsB and LeuO in Escherichia coli - Breddermann, Hannes; Schnetz, Karin (Frontiers in Cellular and Infection Microbiology, 2016)
LeuO is a conserved and pleiotropic transcription regulator, antagonist of the nucleoid-associated silencer protein H-NS, and important for pathogenicity and multidrug resistance in Enterobacteriaceae. Regulation of transcription of the leuO gene is complex. It is silenced by H-NS and its paralog StpA, and it is autoregulated. In addition, in Escherichia coli leuO is antagonistically regulated by the heterodimeric transcription regulator BglJ-RcsB and by LeuO. BglJ-RcsB activates leuO, while LeuO inhibits activation by BglJ-RcsB. Furthermore, LeuO activates expression of bglJ, which is likewise H-NS repressed. Mutual activation of leuO and bglJ resembles a double-positive feedback network, which theoretically can result in bi-stability and heterogeneity, or be maintained in a stable OFF or ON states by an additional signal. Here we performed quantitative and single-cell expression analyses to address the antagonistic regulation and feedback control of leuO transcription by BglJ-RcsB and LeuO using a leuO promoter mVenus reporter fusion and finely tunable bglJ and leuO expression plasmids. The data revealed uniform regulation of leuO expression in the population that correlates with the relative cellular concentration of BglJ and LeuO. The data are in agreement with a straightforward model of antagonistic regulation of leuO expression by the two regulators, LeuO and BglJ-RcsB, by independent mechanisms. Further, the data suggest that at standard laboratory growth conditions feedback regulation of leuO is of minor relevance and that silencing of leuO and bglJ by H-NS (and StpA) keeps these loci in the OFF state.